Kepuasan Tinggi, Partisipasi Menurun: Analisis Perilaku Pemilih pada Pilkada Calon Tunggal Kabupaten Batanghari Tahun 2024 - Delfi Verlita Kurniawan; Aditya Romadhon; Dimasrizal Dimasrizal (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study aims to analyze the effect of public satisfaction on political participation in the 2024 single-candidate regional election (Pilkada) in Batanghari Regency. Political participation in elections is an important indicator of democratic quality, especially in a single-candidate contest where electoral competition is limited. The research employed a quantitative explanatory approach with a sample of 151 respondents selected through simple random sampling. Data were collected using structured questionnaires and analyzed using simple linear regression with IBM SPSS Statistics to determine the relationship between public satisfaction and political participation. The results indicate that public satisfaction has a positive and significant effect on political participation, with a coefficient of determination (R²) of 0.510. This means that 51% of the variation in political participation can be explained by public satisfaction, while the remaining percentage is influenced by other factors not included in this study. However, voter turnout in the 2024 election declined compared to the previous regional election. These findings suggest that public satisfaction is not the sole factor influencing political participation, as the level of political competition in a single-candidate election also plays an important and contextual role in shaping voter behavior and turnout.